The Role of Self-Regulation on the Tendency of Nomophobia in College Students - Patimah, Dwi Siti; Andrianie, Prilya Shanty; Mukti, Patria (Universitas Trunojoyo Madura, 2024)
The advancing development of information and communication technology has resulted in the widespread integration of gadgets into nearly all aspects of daily life and the learning process. The use of gadgets not only facilitates daily activities but, when used excessively, can give rise to adverse consequences, one of which is Nomophobia. Individuals experiencing nomophobia develop a dependency on their smartphones, leading to excessive worry when they are separated from their smartphone or when its battery is depleted. There are several efforts aimed at preventing the emergence of Nomophobia, one of which involves self-regulation. The objective of this research is to examine the role of self-regulation in the predisposition towards Nomophobia among university students. The research design employed is quantitative correlational with a non-probability sampling technique, specifically purposive sampling. The research population comprises 1,411 university students at University X, with a sample size of 93 students determined using the Slovin formula. Data was collected using the Nomophobia questionnaire developed by Yildirim and the Self-Regulation scale by Bandura. Based on the results of hypothesis testing, an R value of 0.288 was obtained (F = 8.230; p smaller than 0.05). Based on the results of data analysis and discussion that has been presented, the results show that self-regulation has a positive effect on nomophobia. The effective contribution of self-regulation to the propensity for nomophobia is 18.3%, while the remaining 81.7% is attributed to other variables or factors. The research findings indicate that 71% of the subjects exhibit high self-regulation, 18.3% possess very high self-regulation, and 10.2% demonstrate moderate self-regulation. As for the tendency towards Nomophobia among the research subjects, 34.4% display a low tendency, 25.8% fall into the moderate category, 20% exhibit a high tendency towards Nomophobia, and 19.8% are classified as having a very high tendency.